Return on investment (ROI) in subscription databases by Nigerian academic libraries: a survey - Oyadeyi, Adekunle Emmanuel; Oladokun, Taofeek Abiodun; Shorunke, Oludare Adebanji; Fasola, Omobolanle Seri (Folia Toruniensia, 2021)
Aim: There seems to be a dearth of literature on how much Nigerian university libraries are spending on the acquisition of Online Electronic Database (OED). This study sets out to investigate the annual cost of acquiring this important and evolving aspect of library collection with the view of determining whether the returns in terms of utilization is commensurate with the invested fund. Methodology: The study adopts a quantitative research method. A self-developed questionnaire was used to collect data from 55 librarians in 41 academic libraries across Nigeria. The data collected were processed using Statistical Package for the Social Sciences (SPSS) version 20. Findings: Academic libraries in Nigeria spend an average of ₦12,500,000 or $32,637 on OED subscriptions annually. The study has shown that Nigerian academic libraries usually subscribe to the EBSCOhost and Research4Life databases with few adding specialized databases such as Law Pavilion, HeinOnline, Legalpedia, and ScienceDirect. To ensure adequate returns on investment, the libraries are massively providing support infrastructures, user education, and other information services. However, challenges limiting the widespread use of online databases include irregular power supply and slow internet connectivity among others. Conclusions: The study, therefore, concludes that there is a middling to low return on subscribed OED in Nigerian academic libraries. However, there are still various huddles that must be scaled for Nigerian academic libraries to reap adequate returns on their investments in online electronic databases.